The Routledge companion to dramaturgy - Romanska, Magda (Routledge companions., 2015)
Dramaturgy, in its many forms, is a fundamental and indispensable element of contemporary theatre. In its earliest definition, the word itself means a comprehensive theory of ""play making."" Although it initially grew out of theatre, contemporary dramaturgy has made enormous advances in recent years, and it now permeates all kinds of narrative forms and structures: from opera to performance art; from dance and multimedia to filmmaking and robotics. In our global, mediated context of multinational group collaborations that dissolve traditional divisions of roles as well as unbend prev.